Pengawasan Badan Pengawas Pemilu (Bawaslu) Dalam Penyelenggaraan Pemilihan Walikota Ddan Wakil Walikota Samarinda 2021-2024 (Studi Tentang Pengawasan Pilkada di Masa Pandemi Covid-19) - Oktavianus Resky Panala; Burhanudin; Erwin Resmawan (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2021)
This study aims to describe Bawaslu's supervision in holding the election for Mayor and Deputy Mayor of Samarinda 2021-2024 during the COVID-19 pandemic and to identify the supporting factors for Bawaslu in holding the election for Mayor and Deputy Mayor of Samarinda 2021-2024 during the COVID-19 pandemic. This research was conducted at the Bawaslu Office in Samarinda City. This type of research is descriptive qualitative and this study uses interactive model qualitative data analysis techniques. The results showed that the supervision carried out by the Samainda City Bawaslu in the 2020 Samarinda City Pilkada during the COVID-19 pandemic at the campaign implementation stage was by fielding field supervisors to check the suitability of campaign implementation during the pandemic, at the stage of monitoring campaign funds Bawaslu carried out supervision with supervision file or cross-check the candidate pair's campaign fund data. In the logistics procurement stage, Bawaslu sent field supervisors to review the suitability of Pilkada logistics during the pandemic, while for the logistics distribution stage, Bawaslu sent supervisors to oversee the distribution of l until it was distributed to TPS. Supervision at the voting and counting stage of the Pilkada results at TPS was carried out by placing PTPS totaling 1,962 people at each TPS equipped with smartphones and official reports to document activities during voting and counting. For monitoring the determination of Pilkada results, the supervision is based on valid verified ballots. Factors supporting Bawaslu supervision are Law No. 7 of 2017 Article 104 Letter F, namely participatory supervision, besides that high public awareness of the health program and an increase in the number of TPS, namely 1,962 to prevent transmission of COVID-19.